Empiricism in non-communicable disease mortality measurement for the Asia-Pacific: lost in translation. Issue 11 (16th November 2020) - Rao, Chalapati; Kelly, Matthew
Abstract : Control of non-communicable diseases (NCDs) is a key target for the United Nations Sustainable Development Goals (SDGs) for 2030. Available information indicates that countries in the Asia-Pacific Region accounted for 63% of the global NCD mortality burden in 2016. The United Nations Economic and Social Commission for the Asia Pacific (UNESCAP) Regional SDG progress report for 2020 included estimates of trends in NCD mortality rates from 2000 to 2016, which showed considerable variation in national NCD mortality by sex and location. However, while the UNESCAP report states that there was sufficient primary data to derive these NCD mortality estimates for all countries, the critical gaps in availability of national data on causes of death in the Asia-Pacific region are well known. A closer review identified that the UNESCAP obtained these estimates from the United Nations Statistics Division, which in turn obtained the same estimates from WHO. Further analysis revealed that these organisations used varying and often inconsistent terms to describe estimation methodology as well as primary data availability for different countries, with substantial potential for misinterpretation. The analysis also found that for countries without primary data, WHO reported NCD mortality estimates were based on complex epidemiological models developed for the Global Burden of Disease (GBD) Study, and this contradicts the UNESCAP rating of primary data sufficiency. The GBD Study also derives modelled cause of death estimates for countries with national data, but these were different from WHO estimates for these countries. This article discusses prevailing international practices in using modelled estimates as a substitute for empirical data, and the implications of these practices for health policy. In conclusion, a strategic approach to strengthen national mortality statistics programmes in data deficient countries is presented, to improve NCD mortality measurement in the Asia-Pacific Region.